Unusual early recurrence of granular dystrophy after deep anterior lamellar keratoplasty: case report - Rama,Paolo (2013)
We report an atypical case of granular corneal dystrophy recurrence after deep anterior lamellar keratoplasty. We describe clinical features, histopathological analysis of the lamellar graft specimen and DNA analysis results. The slit-lamp examination and histopathological findings from the graft specimen indicated the confinement of the typical deposits of granular corneal dystrophy deep in the graft interface area. This localization is atypical, since in most cases recurrences in grafts tend to be initially superficial and situated in the epithelial or subepithelial corneal layers. Molecular genetic analysis revealed an already described mutation and a new intronic variant. The unusual localization and timing of this recurrence of granular corneal dystrophy after deep anterior lamellar keratoplasty suggests that corneal stromal keratocytes may play a role in the formation of granular deposits.